A case study on roundabout capacity and its efficiency at Kota Samarahan - Iswandy, Sureia @ Suri (Universiti Malaysia Sarawak (UNIMAS), 2006)
Modern Roundabouts are very typical design of intersections used in Sarawak. At a very high traffic flow, roundabouts will fail when the traffic demand is exceeding its designed capacity. Thus, this project aimed to determine the capacity of the roundabout using two most popular methods, namely Highway Capacity Manual (HCM) Gap acceptance Method and Linear Regression Based Method, UK. Gyratory 4, which is located at Kota Samarahan was selected as the study site. Traffic volume studies were conducted at the selected study site to obtain the required data for further analysis. From the results obtained, the two methods used showed a quite considerable differences in the outputs. Generally, based on the observation made during the traffic volume data collection, the outputs of UK Empirical method produced a more reliable results compared with HCM Model. By using UK Linear Method, only one arm (7th Mile) exceeds its operational capacity (0.88). Whereas in HCM, v/c ration of right lane for two arms, namely 7`h Mile (5.02) and Serian Road (5.06) produced the highest value. These results are clearly indicated that the roundabout has failed to serve the current traffic demand, which are not true when compared with the actual observed operational capacity. Subsequently, some potential solutions are addressed in this report to be adopted to mitigate the existing situations.